Kar9 symmetry breaking alone is insufficient to ensure spindle alignment - Miram Meziane (Nature Portfolio, 2021)
Abstract Spindle positioning must be tightly regulated to ensure asymmetric cell divisions are successful. In budding yeast, spindle positioning is mediated by the asymmetric localization of microtubule + end tracking protein Kar9. Kar9 asymmetry is believed to be essential for spindle alignment. However, the temporal correlation between symmetry breaking and spindle alignment has not been measured. Here, we establish a method of quantifying Kar9 symmetry breaking and find that Kar9 asymmetry is not well coupled with stable spindle alignment. We report the spindles are not aligned in the majority of asymmetric cells. Rather, stable alignment is correlated with Kar9 residence in the bud, regardless of symmetry state. Our findings suggest that Kar9 asymmetry alone is insufficient for stable alignment and reveal a possible role for Swe1 in regulating Kar9 residence in the bud.